Strategi Komunikasi Massa Dispora Sumsel Dalam Menginspirasi Anak Muda Pada Program Podcast Ngopipora - Novelin Permanda; Eni Murdiati; Muhammad Randicha Hamandia (CV. ITTC INDONESIA, 2024)
DISPORA South Sumatra or known as the Youth Agency is a government agency that focuses on working on the development of young people, youth groups, especially those in South Sumatra. by having an interactive podcast program, namely “NGOPIPORA” which stands for smart chat around DISPORA, this program is a work program that focuses on the media department in the agency which discusses inspirational stories from successful and accomplished young people. DISPORA South Sumatra certainly has a strategy in running its program. This is what makes researchers interested in conducting research with the title DISPORA South Sumatra's strategy in inspiring young people on the NGOPIPORA program as well as to find out the strategies used by DISPORA South Sumatra in inspiring young people and attracting young listeners through the NGOPIPORA podcast program, with the aim of knowing the strategies used by DISPORA South Sumatra in inspiring young people and attracting young listeners through the NGOPIPORA podcast program. This research is a type of research that uses qualitative research methods with descriptive analysis, there are two data sources in this study, namely primary data in the form of 3 informants and secondary data derived from archival documents. This research uses interviews, observation, and documentation as data collection tools and uses the Miles and Huberman model data analysis technique. While the theory used in this research is the theory developed by Susan Tyler Eastman which dissects the broadcast programming strategy in a media into 5 stages, namely compatibility strategy, habbit formation strategy, control of audience flow, conservation of program resources, and breadth of appeal. The results of the study concluded that DISPORA South Sumatra in the strategy of inspiring young people and attracting young people's listening interest through the NGOPIPORA podcast program is to adjust the program based on existing needs and momentum, besides that it also utilizes the latest technology in disseminating its programs ranging from live delay streaming YouTube, social media promotion and scheduled program promotion.